The management of disputed areas and their impact on Iraqi national security after 2003 (قضايا سياسية, 2025)
The disputed territories represent one of the most complex political and security challenges in Iraq after 2003, closely linked to constitutional ambiguities and conflicts between the federal government and the Kurdistan Regional Government. The lack of a definitive legal and constitutional settlement, particularly in Kirkuk, has created fertile ground for political tensions and social divisions, negatively affecting Iraq’s national security. Disagreements over their administration have weakened state authority and generated security vacuums that were exploited by armed and terrorist groups to expand their influence. Addressing this issue through consensual mechanisms based on dialogue, power-sharing, and resource management is a fundamental step toward enhancing national stability and safeguarding Iraq’s unity and sovereignty